Experimentos didáticos para o ensino de estrutura atômica: motivação para o aprendizado no ensino de química - Silveira, Márcio dos Reis da (2018)
This work proposes to educators (specific or related areas) explanatory scripts, how to make and use the experiments in an educational way, about the topics: Photoelectric Effect and Atomic Spectrum, to serve as support and unifying theory with practice. It exposes the experience of the educator, who is experiencing the problems such as evasion, disinterest, demotivation and other aggravating circumstances, which are related to the low levels of student’s participation in physics and chemistry classes, at elementary, high school and higher education with the practice of experimentation, after the theoretical content is exposed. It is shown that, in the National Curricular Proposals of these disciplines, the topics that mainly address the basic concepts pertinent to quantum mechanics are not emphasized. In this way, and through experimental activities with an approach in science, technology, society and environment, it seeks improvement in learning about the fundamental questions of the discipline, encouragement and motivation of students to participate and to teamwork. The research points out as support, this perspective of offering encouragement and motivation, the deepening of the knowledge of students in the areas of physics and chemistry, also seeking to stimulate the educator to diversify their practical classes. The work discusses the construction of experiments with alternative, recycled and low-cost materials, the suggestion of models of experiments, followed by explanatory script for its accomplishment and questionnaire, possibly the most important part of this educational study, which allows the educator to direct the experiments in a didactic and scientific manner simultaneously. The theoretical explanations, applied in a practical way in this context, awaken the interest and expectations in the students and make them understand better how the processes and physical and chemical phenomena occur through experiences performed in different levels of education.